Asian pheretimoid earthworms in North America north of Mexico: An illustrated key to the genera Amynthas, Metaphire, Pithemera, and Polypheretima (Clitellata: Megascolecidae) - Chang, Chih-Han; Snyder, Bruce A.; Szlavecz, Katalin (Zootaxa, 2016)
The invasion of the pheretimoid earthworms in North America, especially the genera Amynthas and Metaphire, has raised increasing concerns among ecologists and land managers, in turn increasing the need for proper identification. However, the commonly used keys to this group are more than 30 years old with outdated taxonomic information and are based primarily on internal morphology. The requirement of significant amount of taxonomic expertise and dissection, even from the first entry of the key, has prevented broader use of these keys. As a result, many publications in the United States have used Amynthas spp. to represent the group without identifying the species. We present here a new key and diagnoses for the 16 pheretimoid earthworm species recorded in North America north of Mexico, including four genera: Amynthas (10), Metaphire (4), Pithemera (1), and Polypheretima (1). The descriptions were based on published records with modifications following inspection of specimens archived at the National Museum of Natural History, Smithsonian Institution, Washington, D.C. Photos of external and internal characters, including male pores, spermathecal pores, genital markings, spermathecae, prostate glands, and intestinal caeca, are presented to help identification. A summary of current knowledge about the ecology and historical context is provided for each species. We also highlight the previously overlooked and potentially common and widespread co-occurrence of three species—A. agrestis, A. tokioensis, and M. hilgendorfi—and point out that many recent claims of invasion of A. agrestis need to be re-evaluated for potential misidentification.